Fascism : theory and practice - Renton, Dave, 1972- (London ; Sterling, Va. : Pluto Press, 1999)
Annotation In the 1930s fascist parties came to power across Europe. Millions were killed in the war and the Holocaust. Yet, sixty years on, fascism is on the rise once more in all major European states and far right parties are again winning converts. To explain this disturbing trend, Dave Renton surveys the history of modern fascism in Europe, from its prewar origins up to the present day. Renton examines the Marxist response to fascism in the age of Hitler and Mussolini and the writings of political thinkers such as Trotsky and Gramsci, as well as more recent European theorists such as Miliband, Mason and Poulantzas. Focusing on a critical assessment of the current liberal theories of fascism which emerged in the 1980s and 1990s, the author argues that such theories provide an incomplete explanation of what fascism is and was: to understand any political movement it is vital to view it in a historical context. Renton argues that fascism should be understood not through the 'theory' of liberal fascism studies, but rather in terms of the brutal practice that fascism brought in its wake. Providing the first new theory of fascism in its historical context to come from the left for over twenty years, this volume makes a key contribution to what is now a wide-ranging and heated debate.
Fascism Today -- The Prison Of Ideas -- Classical Fascism -- An Alternative Method -- Marxists Against Mussolini And Hitler -- Thalheimer, Silone, Gramsci, Trotsky -- Beyond 1933 -- Marxists and The Holocaust -- Conclusion.
Includes bibliographical references (pages 117-146) and index.
Print version record.
English.
JSTOR
Keywords: Fascism; Fascism -- Europe -- History; Fascisme; Fascisme -- Europe -- Histoire; fascism; POLITICAL SCIENCE -- Political Ideologies -- Fascism & Totalitarianism; HISTORY -- Modern -- 20th Century; Fascism; Europe; Politische Theorie; Praxis; Faschismus; Europa; Fascisme -- Europe; History